Building Digital Tolerance Through Artificial Intelligence (AI) and Quranic Values - Tasya Arnestya Santika; Muhammad Wildan Shohib (Universitas Muhammadiyah Surakarta, 2025)
This research aims to profoundly analyze the role of Artificial Intelligence (AI) in fostering digital tolerance and its integration with the fundamental values derived from the Qur’anic verses. The research employs a library research (literature review) methodology, utilizing a philosophical approach to examine the concepts of tolerance and the ethical implementation of technology. The primary data source is Abdul Mu’ti book, “Authentic Tolerance” complemented by various relevant secondary source. Tolerance is defined as the attitude of accepting and respecting differences across religion, ethnicity, race, and life perspectives. The attitude plays a crucial role in creating peace and stability within pluralistic societies. The relevance of this concept extends from daily social interactions to the rapidly evolving digital era. Communication technology, especially social media, serves as a platform bringing together individuals from various backgrounds, promoting mutual understanding and harmonious relationships. In this context, digital tolerance becomes essential and can be realized through the use of AI as a means to anhance inclusive religious awareness and promote tolerant attitude. Islam emphatically teaches the importance of tolerance, reflected in the Qur’anic teachings that encourage respect for diversity (ikhtilaf) and freedom of religion. In the digital landscape, the wise use of technology is strongly emphasized to prevent the spread of conflict triggering information, and crucically, to prioritize the principle of tabayyun (verification/clarification) to ensure informational truth. The findings of this study indicate that AI can be effectively utilized as an information filter and a content recommendation system designed based on the values of moderation and harmony. Specifically, the ethical values from the Qur'an, such as the principle of ta'aruf (mutual knowing) and the divine words lakum dinukum waliyadin (to you is your religion, and to me is my religion), serve as the primary philosophical foundation for designing humanistic and tolerant AI architecture and algorithms. This methodological integration is achieved through a comparative study and deep interpretation of contemporary AI concepts and relevant Qur'anic principles, culminating in the formulation of a framework for digital tabayyun and responsible digital ethics. Therefore, building tolerance in both real and digital spaces requires a collective effort that prioritizes the values of mutual respect and shared responsibility.